Surgical Site Infection (SSI) - Kinga Rogowska; Aleksandra Romanowska; Aleksandra Padkowska; Michał Borawski; Aleksandra Ciuła; Klaudia Arciszewska; Jakub Maciej Pieniążek; Mateusz Dobosz; Jakub Buczkowski; Weronika Biaduń (Journal of Education, Health and Sport)
Surgical Site Infections (SSIs) are a significant complication of invasive surgical procedures, contributing to increased morbidity, mortality, and healthcare costs globally. Despite advancements in surgical techniques, hygiene practices, and the implementation of infection control protocols, SSIs remain a critical issue in postoperative care. This document provides a comprehensive overview of SSIs, including their definition, causes, risk factors, and microbiology. The primary pathogens responsible for SSIs are Gram-positive bacteria and fungi, with specific concern for immunosuppressed patients who are at increased risk for opportunistic infections. The classification of SSIs based on wound cleanliness and depth is essential for determining the appropriate treatment strategy, which may include drainage, surgical debridement, and the use of local or systemic antibiotic therapy. The document also highlights the importance of preventive measures, including rigorous perioperative antibiotic prophylaxis and adherence to established surgical protocols, to reduce the incidence of SSIs. The discussion is supported by data from various studies and clinical guidelines, emphasizing the need for ongoing vigilance in infection control practices to mitigate the impact of SSIs on patient outcomes.